Digital Natives Acceptance of Near Field Communication (NFC) Mobile Payment - Yap Chien Wen; Norasmiha Mohd Nor (Research in Management of Technology and Business, 2024)
The proliferation of smartphones has inspired innovations like Near Field Communication (NFC) mobile payments to substitute cash, cards and cheques. However, the adoption rate of NFC mobile payments among the digital natives in Malaysia is low attributing it to their unfamiliarity with digital platforms. This study aims to investigate the factors (perceived usefulness, perceived ease of use, and perceived risk) determining the intention to use NFC mobile payments among digital natives in Malaysia. The research methodology included a self-administered questionnaire and snowball sampling procedure on social networks distributed among Generation Y (age 13-28) and Generation Z (age 29-43). A cross-sectional was undertaken on a sample of 500 NFC mobile payment users for the study. The data was collected and analyzed using the Statistical Package for Social Science (SPSS). The results of the analysis reveal that perceived usefulness, perceived ease of use, and perceived risk have a significant relationship towards the intention to use NFC mobile payment. Therefore, the study underlines the key factor influencing the adoption of NFC mobile payment as perceived risk. Digital natives are more accustomed to digital technologies and would find NFC mobile payment as convenient, speedy, and flexible that compatible with their lifestyle.